Examining the Effects of Perceptions of Voter Suppression and Voter Fraud on Support for Voter Identification Laws in the United States - Basham, Sherah L.; Acuff, Christopher; Iles, Gale; Brown, Samuel L.; Hyppolite, Jennah (International Journal of Criminology and Sociology, 2023)
Democracy is fundamentally grounded in the people’s right to vote, but what happens when the same mechanisms meant to protect the electoral process become barriers? This study examined the relationship between perceptions of voter suppression and voter fraud and support for voter restrictions, such as requiring identification to vote. The study utilized data from the American National Election Studies 2020 Times Series Study, examining a sample of 5,264 voters. Results revealed that voter support for voter ID laws depends on their perceptions of voter integrity and suppression. The more confidence voters have in the integrity of elections and the more they believe in voter suppression, the less likely they are to support voter identification requirements. Other demographic factors are considered.